The potency of Immunoglobulin Y anti Porphyromonas gingivalis to inhibit the adherence ability of Porphyromonas gingivalis on enterocytes - Nova Andriani Hepitaria; Indeswati Diyatri; Markus Budi Rahardjo; Rini Devijanti Ridwan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Pophyromonas gingivalis (P. gingivalis) bacteria are the main type of bacterium that cause chronic periodontitis. Immunoglobulin Y (IgY) is a type of immunoglobulin found in poultry, such as chickens and birds. IgY can be used as an alternative method of preventing the accumulation of plaque that causes chronic periodontitis. Purpose: To determine the ability of IgY anti P. gingivalis to inhibit adherence of P. gingivalis. Methods: The samples were divided into eight groups, each group containing 10 ml of IgY anti P. gingivalis and 50 ml of enterocyte cells. The control group contained 50 ml of IgY anti P. gingivalis, and 50 ml of enterocyte cells. Serial dilution was carried out to the first seven groups, with the first group containing 90 ml phosphate-buffered saline (PBS) and 10 ml IgY anti P. gingivalis, and the second to seventh groups containing 50 ml PBS before adding 50 ml of enterocyte cells and 50 ml of bacterial suspension per group. The number of bacteria was calculated as an adherence index value using a light microscope. Results: This study shows that IgY anti P. gingivalis significantly reduces the adherence index value of P. gingivalis. Conclusion: IgY anti P. gingivalis has potency to inhibit the adherence of P. gingivalis.